The A-Z of social research a dictionary of key social science research concepts - Miller, Robert L. (Robert Lee), 1948-; Brewer, John D. (London : SAGE, 2003)
Alphabetically arranged in accessible, reader-friendly format this collection of 94 entries provides a concise introduction to the key concepts and methods in social research.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research